Massive Lipomatosis of the Small Intestine Causing Intussusception - Michael Pagacz; Irvin Willis; John Alexis (Case Reports in Gastrointestinal Medicine)
Lipomatosis is a rare condition characterized by diffuse, unencapsulted adipose tissue deposition. Intestinal involvement is rare, and presentation as intussusception is rarer still. We report a 40-year-old man who presented with abdominal pain and fecal urgency. Abdominal CT scan showed a protuberant ileo-cecal valve, with intussusception of the ileum into the cecum. The mucosal surface of the resected bowel was bulbous and protuberant, showing loss of mucosal folds, and there was an 8 × 5 × 5 cm mass prolapsing into the ileo-cecal valve. Microscopically there was abundant adipose tissue in the submucosa with an unremarkable mucosa. The patient recovered uneventfully with only occasional cramping in the left abdomen.